2018
DOI: 10.1016/j.soard.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant weight loss medication after bariatric surgery

Abstract: Adjuvant weight loss medications halted weight regain in patients who underwent bariatric surgery. More than one third achieved>5% weight loss with the addition of weight loss medication. The observed response was significantly better in gastric bypass and gastric banding patients compared with sleeve gastrectomy patients. Furthermore, adjuvant pharmacotherapy was more effective in patients with higher body mass index. Given the low risk of medications compared with revisional surgery, it can be a reasonable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 25 publications
9
62
1
3
Order By: Relevance
“…The studies which have primarily examined the use of phentermine, phentermine/topiramate, and naltrexone/bupropion, and report no differences for patients who had undergone RNYGB and AGB. However, individuals who had undergone gastric sleeve lost less weight than those who had undergone RNYGB and AGB . Consistent with previous literature, we did observe similar reductions in weight while taking liraglutide 3.0 mg for patients who had undergone RNYGB or AGB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The studies which have primarily examined the use of phentermine, phentermine/topiramate, and naltrexone/bupropion, and report no differences for patients who had undergone RNYGB and AGB. However, individuals who had undergone gastric sleeve lost less weight than those who had undergone RNYGB and AGB . Consistent with previous literature, we did observe similar reductions in weight while taking liraglutide 3.0 mg for patients who had undergone RNYGB or AGB.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, there is no weight management pharmaceutical approved for use in patients who have had bariatric surgery as having had bariatric surgery is often an exclusion for non‐surgical weight loss trials. However, research on the off‐labelled prescription of weight management pharmaceuticals in post‐bariatric surgery patients have reported significant decrease in weight post‐initiation of these agents . Consistent with these findings, post‐bariatric surgery patients in the current study taking liraglutide 3.0 mg lost a significant amount of weight.…”
Section: Discussionsupporting
confidence: 83%
“…There were differences in the study design of the 13 articles included in this review. Eleven of the studies were cohort studies 4,[7][8][9][10][11][12][13][14][15][16] , and the remaining two are a matched prospective cohort 17 and case series 18 . Types of bariatric surgery procedures also varied, but the most common procedure was roux-en-y gastric bypass (RNY), in ten [7][8][9][10][11][12][13]15,16,18 studies, followed by adjustable gastric banding (AGB) 4,10,12,13,[15][16][17] and sleeve gastrectomy (SG) [7][8][9][10]12,13,15 both in seven studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [7][8][9]11,13 examined weight loss outcomes by the type of bariatric surgery procedure. Four studies reported less weight loss for patients who have undergone SG compared to AGB 13 (p ¼ .02) and RNY [7][8][9]13 when taking weight loss pharmaceuticals. Two of these four studies were posthoc analysis of an original study 9 and showed the same consistent pattern in younger (21-30 years; p ¼ .05151) 8 and older (!60 years; p ¼ .03) 7 adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation